Materiais cerâmicos para células a combustível - Florio, D. Z. De [UNESP]; Fonseca, F. C.; Muccillo, E. N. S.; Muccillo, R. (Associação Brasileira de Cerâmica, 2004)
Basic definitions of fuel cells and a brief introduction of different types of fuel cells are given. A review of the most important ceramic materials being considered for the design and fabrication of devices for producing electrical energy is presented. Ceramic materials with suitable electrical behavior to be used as electrolytes, anodes, cathodes, interconnectors, and sealants of solid oxide fuel cells are reported with details, taking into account the large number of available indexed and refereed scientific publications and patents. Finally, an evaluation of the state of the art of the research and development of ceramic materials for solid oxide fuel cells is presented.

A partir da definição de células a combustível, é feita uma introdução sucinta dos tipos de células e dos materiais cerâmicos que são empregados em projeto e fabricação destes dispositivos geradores de energia elétrica. Tomando por base a ampla literatura científica disponível em publicações periódicas internacionais indexadas e arbitradas, bem como patentes, são relatados com detalhes os materiais cerâmicos com comportamento elétrico adequado para uso como eletrólitos, anodos, catodos, interconectores e selantes, que são os componentes básicos de células a combustível de óxidos sólidos. Por fim, é feita uma avaliação do estado da arte na pesquisa e desenvolvimento de materiais cerâmicos para uso em células a combustível de óxidos sólidos.
Ceramic materials for fuel cells
Keywords: fuel cells; solid electrolyte; anode; cathode; interconnector; célula a combustível; eletrólito sólido; anodo; catodo; interconector